Distribution, Status, and Conservation of the Indian Peninsular Wolf - Jhala, Yadvendradev; Saini, Swati; Kumar, Satish; Qureshi, Qamar (Frontiers in Ecology and Evolution, 2022)
An understanding of the distribution range and status of a species is paramount for its conservation. We used photo-captures from 26,838 camera traps deployed over 121,337 km2 along data from with radio-telemetry, published and authenticated wolf sightings to infer wolf locations. A total of 3,324 presence locations were obtained and after accounting for spatial redundancy 574 locations were used for modeling in maximum entropy framework (MaxEnt) with ecologically relevant covariates to infer potentially occupied habitats. Relationships of wolf occurrence with eco-geographical variables were interpreted based on response curves. Wolves avoided dense wet forests, human disturbances beyond a threshold, arid deserts, and areas with high top-carnivore density, but occurred in semi-arid scrub, grassland, open forests systems with moderate winter temperatures. Potential habitat that can support wolf occupancy was 364,425 km2 with the largest wolf habitat available in western India (Saurashtra-Kachchh-Thar landscape 102,837 km2). Wolf habitats across all landscapes were connected with no barriers to dispersal. Breeding packs likely occurred in 89,000 km2. Using an average territory size of 188 (SE 23) km2 India could potentially hold 423 to 540 wolf packs. With an average adult pack size of 3 (SE 0.24), and a wolf density < 1 per 100 km2 in occupied but non-breeding habitat a wolf population of 3170 (SE range 2568 to 3847) adults was estimated. The states of Madhya Pradesh, Rajasthan, Gujarat, and Maharashtra were major strongholds for the species. Within forested landscapes wolves tended to avoid top-carnivores but were more sympatric with leopards and dhole compared to tigers and lions. This ancient wolf lineage is threatened by habitat loss to development, hybridization with dogs, fast-traffic roads, diseases, and severe persecution by pastoralists. Their status is as precarious as that of the tiger, yet focused conservation efforts are lacking. Breeding habitat patches within each landscape identified in this study should be made safe and free of feral dogs so as to permit packs to breed and successfully recruit individuals to ensure wolf persistence in the larger landscape for the long-term.